An Overview of Freshwater and Marine Finfish Aquaculture in Spain: Emphasis on Regions. Issue 2 (3rd April 2018) - Muñoz-Lechuga, Rubén; Sanz-Fernández, Víctor; Cabrera-Castro, Remedios
ABSTRACT: Aquaculture is growing at an accelerating pace due to globalization and the disproportionate increase in human population growth in past decades. Thus, it has become one of the main sources of food globally due to its production capacity which, predictions suggest, could surpass extractive fishing in a few years. This situation has led to the fact that, within the sector, fish aquaculture production is the most important reaching 50% of the total production, where freshwater finfish are predominant, accounting for 96% of finfish aquaculture production globally. Despite this global scenario, in the past 10 years Spain has kept developing an opposing strategy to that of the rest of the world, supporting marine production at the expense of freshwater production, in spite of the high finfish aquaculture potential of the country. A new strategy would allow boosting the freshwater finfish aquaculture sector, at the same time investment has been made on marine production. A change in the productive mentality of the country would open up the possibility of reaching, at least, the same levels of total freshwater finfish aquaculture production of some neighboring countries such as France or Italy. In this paper the evolution of freshwater and marine fishing in Spain is analyzed, placing emphasis on some aspects such as the productive potential, species diversification, production at national and regional level, as well as commercialization.